Damage detection method for RC members using local vibration testing. (1st January 2019) - Naito, Hideki; Bolander, John E.
Highlights: A local vibration testing method is proposed using a portable vibrator. Void locations within concrete can be identified from the local resonant frequency. The testing method can be applied to RC members covered with carbon fiber sheets. Wave propagation analyses and the experimental results were in good agreement. The testing method can be applied for the detection of damage within real RC decks. Abstract: A portable vibrator was used to conduct forced vibration testing of concrete members to determine damage locations and conditions within structural concrete. In particular, a local vibration testing method was proposed, along with a numerical means for characterizing the test results. In reinforced concrete (RC) beam specimens with a void, the local resonant frequency decreased over the void region as its length increased. This implies that the void locations and conditions can be identified from the resonant frequency distribution obtained from local vibration testing. Furthermore, in RC beam specimens reinforced with carbon fiber sheets, internal voids can be also identified using the testing method, even though one face of the RC member is covered with the sheets. From the experimental data, the effective region of the local vibration testing is approximately equal to the sectional height. The wave propagation analyses were conducted using a finite difference time domain (FDTD) method, and a simple local calculation model was proposed. Through comparisons with the experimental results, it is shown that the local model can estimate void location and length with good accuracy. From statistical comparisons between the experimental and calculated resonant frequencies, in the intact regions, the mean value of the resonant frequency ratio and its coefficient of variation were 1.03 and 2.8%, respectively. These low values demonstrate the accuracies of both experimental testing method and simple calculation model. On the other hand, in the void region, these values were 0.97 and 17.5%, respectively. As a practical example, the local vibration tests were conducted on a portion of a deteriorated RC deck, which was removed from a bridge structure. In the tests, it was shown that the local resonant frequency is decreased by horizontal cracking within the deck section. Moreover, the resonant frequency distribution of the removed deck was determined. The coefficient of variation of the resonant frequency in intact regions was 5.2%, which is not far from the value (2.8%) obtained for the cast specimens. This indicates that the proposed testing method can be applied for the detection of damage within RC decks.